Digital transformation of industrial production in the context of Industry 4.0 - Tashenova, L.V.; Babkin, A.V.; Mamrayeva, D.G. (BUKETOV BUSINESS REVIEW, 2019)
The article explores the key components of the digital transformation of industrial production in the context of Industry 4.0, in particular: the introduction of IT technologies, which involve the using of Big Data, Blockchain technologies in production, robotics, computer-aided design systems, resource planning of industrial cluster enterprises, product life cycle management, and also process of the control systems of the production processes. An in-depth analysis of the number and content of scientific papers devoted to the research of the digital and innovative potential of the industrial cluster, indexed on the bases of Web of Science, Scopus, the Russian scientific citation index, has been carried out. This analysis revealed the relevance and depth of research, the definition and modern approaches to assessing the digital potential. The approaches, main indicators, and indicators for assessing digital potential proposed by Russian scientists A.V. Kozlov, A.B. Teslya, N.V. Gorodonova and A.A. Peshkova, Yu.A. Kovalchuk, I.V. Alekseyev and others. The author’s definition of the concept «digital potential of an innovative-active industrial cluster» was given, the possible ways of its functioning were highlighted: provided that the traditional production process can be implemented, as well as with the active formation and development of digital potential. The concepts of the digital economy were also characterized and the directions of technology application in industrial production were defined: the «Internet of Things», «Big Data», «Blockchain» and «Cyberphysical Systems».